Analisis Sistem Penanganan Arsip Rekam Medis di Rumah Sakit Bhakti Kartini - Hetmylia Kusumawati; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Journal of Educational Innovation and Public Health, 2024)
The aim of this research is to analyze the handling of medical record archives that runs at Bhakti Kartini Hospital and is the subject of research discussion. This research uses a qualitative method with a descriptive approach, the subjects of this research are the medical records staff at Bhakti Kartini Hospital, totaling 4 people. From the results of the research conducted, Management of medical record archives includes creating, handing over and destroying medical record archives. Maintenance of medical record archives is carried out by medical record staff and maintenance of equipment that supports the archives is carried out by hospital cleaning staff, however, the equipment facilities that support medical record archives are still inadequate, hampering employee activities and performance that are less than optimal. Meanwhile, the storage of medical record archives at Bhakti Kartini Hospital uses a decentralized system where active archives and inactive archives are stored in different storage locations, active archives are less than 5 years old while inactive archives are more than 5 years old, and for the record archive alignment system medical devices use a digit terminal system.